NOVELTIES IN MEDICAL TREATMENT OF GLAUCOMA - Cornel, Ştefan (Rom J Ophthalmol, 2015)
The purpose of this study is to review the current medical treatment and the new and better alternatives for patients with glaucoma. Glaucoma refers to a group of related eye disorders that have in common an optic neuropathy associated with visual function loss. It is one of the leading causes of irreversible blindness worldwide. Glaucoma can damage vision gradually so it may not be noticed until the disease is at an advanced stage. Early diagnosis and treatment can minimize or prevent optic nerve damage and limit glaucoma-related vision loss. Nowadays, research continues for the improvement of current medical treatment.